Exploring Global Trends in Otorhinolaryngology Research Output - Saberi, Mohammad Karim; Mokhtari, Heidar; Farhadi, Arezoo; Ouchi, Ali; Shamloo, Zahra; Haseli, Davoud (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: As an interdisciplinary field, bibliometrics analyses research publications in scientific fields. As a developing medical field, otorhinolaryngology needs to be evaluated from a bibliometric perspective. Aim: This evaluative bibliometric study aimed at analyzing and exploring global research trends in otorhinolaryngology from the beginning to year 2021. Methods: All papers published in otorhinolaryngology field that indexed in Web of Science (WoS) from 1976-2021 were extracted for analysis by conducting a certain search strategy in advanced search section within category of otorhinolaryngology in the WoS. Data were analyzed by Excel and VOSviewer for measuring bibliometric indicators and depicting visualization maps. Results: 217,027 papers were published during the studied time span. The papers increased from two items in the beginning in 1976 to 9,759 items in 2021. USA ranked first with publishing 75,742 papers, followed by Germany with 17,718 papers and England with 14,244 papers. League of European Research Universities (LERU) ranked first among research institutes with publishing 6,517 papers. In journals, Laryngoscope ranked first with publishing 17,891 papers, followed by Otolaryngology-Head and Neck Surgery with 14,340 papers and Journal of Laryngology and Otology with 11,219 papers. The majority of papers were in English (n=199,069; %91,725) and original articles (n=167,724; %77.28). After otorhinolaryngology as the first-ranked area with full coverage, surgery (n=37,586) and audiology speech language pathology (n=22,136) ranked second and third, respectively. 10 highly-occurred keywords were surgery (110), management (94), children (83), quality of life (81), squamous-cell carcinoma (78), cancer (75), head (73), radiotherapy (69), cochlear implant and noise (58) and experience (53), respectively. Co-citation clustering showed Journal of the Acoustical Society of America, Laryngoscope, Otolaryngology–Head and Neck Surgery and Journal of Allergy and Clinical Immunology as the top cited sources. Conclusion: This study is the first to give a comprehensive bibliometric analysis and visualization of global research publication in otorhinolaryngology. It recognized important and influential papers, journals, authors, research institutions, countries and topic areas as well as main considerable keywords and subject clusters and cited sources.